ANALISIS YURIDIS PERALIHAN TANAH HAK GUNA BANGUNAN YANG MASA HAKNYA SUDAH BERAKHIR MELALUI PROSES PEWARISAN DITINJAU MENURUT UNDANG-UNDANG POKOK AGRARIA NOMOR 5 TAHUN 1960 : (Studi Penelitian Pada Kantor Notaris dan PPAT Di Kabupaten Banyuwangi) - Clarisa Hanez, Chintya; Pasaribu, Agnes; Brian Wicaksono, Demas (JURNAL AMAR, 2023)
Abstract: Juridical Analysis Of Land Transition Of Building Usage Rights Which The Term Of Rights Have Ended Through The Insurance Process Reviewed According To Law Principles Of Agrarian Number 5, 1960. (Research Study At The Notary Office And Ppat In Banyuwangi). Land rights are something that is important for today's society. Land rights are specifically regulated in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, hereinafter referred to as UUPA. Land rights according to the UUPA itself are sourced from Article 33 paragraph (1) of the 1945 Constitution, and of course the Right to Build is also included in the ownership rights that must be owned by a person in order to be valid proof of ownership. The transfer of building use rights can occur and this transition can take the form of buying and selling, grants or exchanges and also inheritance. This study uses empirical research methods. Empirical research is data obtained directly from sources by conducting research in the field through observation and interviews related to research and practice. Regarding the process of resolving the problem of building use rights whose rights period has expired through the inheritance process and the obstacles that occur related to building use rights whose rights have expired through the inheritance process. The results of this study are: Building use rights have expired before the inheritance is carried out and there is no clarity and certainty regarding the extension of the rights, then the land will return to the state, and must make a special application for registration of the land by making a new application, not by extending it. existing rights. However, whether the process is long or not, whether it is complicated or not, it also depends on the local Land Agency which will take care of the matter together with the local Notary/PPAT and the obstacles that occur are a reflection of the delay in extending the Building Rights.